A clinical observational study on the efficacy of subcutaneous etonogestrel implants for adenomyosis in 20 patients. (3rd August 2021) - Nie, Lekai; Zou, Hongli; Ma, Xiaotian; Cheng, Lei; Jiao, Jun; Wang, Fenghua; Liang, Weifeng; Zhang, Peihai
Abstract: Objective: To evaluate the efficacy of subcutaneous etonogestrel implants for adenomyosis. Methods: We conducted a clinical observational study of 20 patients suffering from adenomyosis treated with subcutaneous etonogestrel implants from August 2015 to July 2017 and followed up for 36 months. We evaluated the efficacy of subcutaneous etonogestrel implants primarily based on the following indicators: the pictorial blood loss assessment chart (PBAC) for menstrual blood volume, changes in bleeding patterns, the visual analog scale (VAS) pain score for dysmenorrhea, uterine volume, serum cancer antigen 125 (CA125) levels, hemoglobin levels and side effects. Results: During the 3 years of follow-up, subcutaneous etonogestrel implants were removed from six patients, among whom one was diagnosed with endometrial cancer, four had an increased menstrual blood volume, and one entered menopause. In total, 14 patients were treated with subcutaneous etonogestrel implants for 3 years. Among these patients, the number of patients with heavy menstrual bleeding and high PBAC and VAS scores and serum CA125 levels was significantly decreased after implantation compared with that before implantation. In the eight patients with anemia, hemoglobin levels increased gradually. However, the uterine volumes did not significantly change. Bleeding patterns were changed but were tolerable. Conclusion: Subcutaneous etonogestrel implants represent a new option for the clinical treatment of adenomyosis for patients who refuse surgery.